Thickness of the ligamentum flavum of the spine and its relationship with disc degeneration - Mattar,Thiago (2014)
Objective: This study investigates whether the thickening of the ligamentum flavum (LF) is correlated with disc degeneration. Methods: This retrospective study was conducted with 98 patients with chronic low back pain treated in a spinal surgery service between January 2012 and January 2013. All patients underwent magnetic resonance imaging (MRI) and the images were evaluated by a spinal surgeon to measure the thickness of the LF and evaluate the degree of disc degeneration by the Pfirrmann grading system, according to the spinal levels (L3 -L4, L4-L5, L5-S1). An association was sought between LF hypertrophy and disc degeneration, age, sex and disc height. Results: The mean age of the patients was 53.6 years, and the majority were women (59.2%). The thickness of the LF and disc height varied according to the spinal level, the greatest LF thickness being found between L4-L5, and the greatest disc height at L5-S1. Women had statistically thicker ligaments in L3/L4 than men. The degree of disc degeneration was inversely correlated with the height at all the levels evaluated, i.e., the greater the degree of degeneration, the lower the disc height. Conclusions: The thickening of LF is not related to disc height or degree of disc degeneration. Therefore, there is no deformation of the LF within the spinal canal secondary to disc degeneration.